2x + 4 = 362x = 36 - 42x = 32x = 32/2X = 16
If 4x + 4 = 2x + 36 then:4x - 2x = 36 - 4 (we have moved the "x's" all to one side and the constants [the numbers] to the other side; remember we must reverse the sign, e.g. change a plus to a minus, when moving something from one side of the equation to the other).We can now simplify this to:2x = 32Therefore:x = 32/2x = 16.
answer is 4 7x+19=-2x+55 +2x +2x 9x+19= 0 55 -19 -19 9x = 36 9 9 =4
8x-4
x equals 4
2x + 4 = 362x = 36 - 42x = 32x = 32/2X = 16
If 4x + 4 = 2x + 36 then:4x - 2x = 36 - 4 (we have moved the "x's" all to one side and the constants [the numbers] to the other side; remember we must reverse the sign, e.g. change a plus to a minus, when moving something from one side of the equation to the other).We can now simplify this to:2x = 32Therefore:x = 32/2x = 16.
What is X if 2x + 4 = 36 What is X ? 2x + 4 = 36
No 9xx-18x+36 9(xx-2x+4) xx-2x+4 (doesn't factor evenly)
answer is 4 7x+19=-2x+55 +2x +2x 9x+19= 0 55 -19 -19 9x = 36 9 9 =4
6x3 - 27x2 + 3x + 36 = 3 (x - 4) (x + 1) (2x - 3)
x2+12x+36=0 2x+12x+36=0 14x+36=0 14x=-36 x=-36/14 x=-2 4/7
8x-4
x equals 4
2x+4+7x-4 is the same as 9x
-2x^4+16 +2x^4+9-3x^5=-3x^5+25. There is no "answer" because there is no equation.
2x + x + 4 +2x = x + 20 5x + 4 = x + 20 5x - x = 20 - 4 4x = 16 x = 4